-4(4w-3)+2w=4(w+5)

Simple and best practice solution for -4(4w-3)+2w=4(w+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(4w-3)+2w=4(w+5) equation:



-4(4w-3)+2w=4(w+5)
We move all terms to the left:
-4(4w-3)+2w-(4(w+5))=0
We add all the numbers together, and all the variables
2w-4(4w-3)-(4(w+5))=0
We multiply parentheses
2w-16w-(4(w+5))+12=0
We calculate terms in parentheses: -(4(w+5)), so:
4(w+5)
We multiply parentheses
4w+20
Back to the equation:
-(4w+20)
We add all the numbers together, and all the variables
-14w-(4w+20)+12=0
We get rid of parentheses
-14w-4w-20+12=0
We add all the numbers together, and all the variables
-18w-8=0
We move all terms containing w to the left, all other terms to the right
-18w=8
w=8/-18
w=-4/9

See similar equations:

| 4/3w=28 | | 8=-4(-3+c) | | 11a−5a=18 | | 9^x+3=5x | | 7x+7/10=28 | | 1.75x-132.49=369.76 | | 8=−4(−3+c) | | $1.75x-$132.49=$369.76 | | 3(u-8)-6=-3(-9u+6)-8u | | 13q-8q+1=11 | | 5+8b=29 | | x32=1.5 | | 184=-8(7+4y) | | 3v+5=24 | | 8h-5h=9 | | 11w+66=-71 | | x/12=68 | | -16x^2-33x-16=0 | | 7n-35=2n+26 | | 16-2n=-8+4(1n-3) | | 3(x+4)-2(x+1=0 | | 7-3x+8x=2 | | q=16÷4 | | -16+11=h | | 4(x+6)+2(-x+6)=-10 | | 4x=27=75 | | 3x+6+2x-1=4x-5 | | p=4−-14 | | 9w=35+4w | | 11=-3+2q | | 7x+30+9x+42=90 | | 3=m+5/5 |

Equations solver categories